An Analytical Study of Discarded Units of Whole Blood and its Components in a Blood Bank at a Tertiary Care Hospital in Vadodara (Global Journal of Medical Research, 2020)
Background: Blood is precious and there is no alternative for human blood. Proper utilization as well as rationale use of blood is necessary with minimal discarding of blood units and implementing various interventions that can be used to optimize blood and its components use by training and education.